(untitled) (Philological Studies, 2019)
The objective of this work is an attempt to show the specificity of deixis of personal pronoun I in the political discourse on the materials of the Czech National Corpus. From a semantic point of view this category attracted a lot of attention, particularly egocentrism and the functional semantic field of personality. First I want to designate the place of the personal pronoun I in the functional semantic field of personality, I want to show their substitutive words components with his specifics in the context of both languages translation and at the same time look at how corpus search engine identifies it.